2020
DOI: 10.1002/ags3.12355
|View full text |Cite
|
Sign up to set email alerts
|

A novel risk‐scoring system for predicting lymph node metastasis of rectal neuroendocrine tumors

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…We showed that tumor size greater than 11.5 mm and vascular invasion were independent risk factors for lymph node metastases. Nevertheless, despite what is reported in the current ENETS guidelines, our investigation lowered the dimensional cutoff for clinical decisions from 20 mm to 11.5 mm in line with the results from the latest retrospective analyses regarding r-NETs [13,[32][33][34][35]. Similar to our findings, two large retrospective studies based on national registries published in 2019 and a retrospective report from the French group of endocrine tumors (GTE) confirmed that tumor size larger than 10 mm was related to nodal involvement in non-metastatic r-NETs, along with other predictive factors, such as tumor grade and presence of muscular and lymphovascular invasion [33][34][35].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…We showed that tumor size greater than 11.5 mm and vascular invasion were independent risk factors for lymph node metastases. Nevertheless, despite what is reported in the current ENETS guidelines, our investigation lowered the dimensional cutoff for clinical decisions from 20 mm to 11.5 mm in line with the results from the latest retrospective analyses regarding r-NETs [13,[32][33][34][35]. Similar to our findings, two large retrospective studies based on national registries published in 2019 and a retrospective report from the French group of endocrine tumors (GTE) confirmed that tumor size larger than 10 mm was related to nodal involvement in non-metastatic r-NETs, along with other predictive factors, such as tumor grade and presence of muscular and lymphovascular invasion [33][34][35].…”
Section: Discussionsupporting
confidence: 81%
“…The incidence of r-NETs has been increasing in recent decades and, despite the overall good prognosis, the long-term prognosis of r-NETs is comparable to that of colorectal cancer in the case of nodal involvement [13,18,19]. Thus, a risk stratification-based approach could suggest the appropriate surgical or endoscopic management in this setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been fewer studies regarding the tumor grade than other factors because these grades were first described in the WHO classification of digestive system tumors in 2010 [ 11 ]. While some studies have reported that the tumor grade was a significant predictor [ 6 , 9 , 13 ], others have concluded that the tumor grade did not play a part in prediction of LNM [ 14 ]. In this study, 83% (5/6) of the patients with tumor grade 2 had LNM.…”
Section: Discussionmentioning
confidence: 99%
“…9,29,31,35,36 Correlation between tumour size and lymphovascular invasion has also been demonstrated with a tumour size ≥5 mm at higher risk of lymphovascular involvement than in tumours with a size <5 mm, 36 and predictive scores taking into account both, the tumour size and the lymphovascular involvement have been shown to provide an accurate assessment of the risk of metastatic lymph node involvement. 37,38 Computed tomography (CT) has limited value for the detection and characterisation of regional metastatic lymph nodes in patients with rNET. 39 Similarly to rectal adenocarcinoma, MRI with diffusionweighted imaging (DWI) is considered as the most sensitive imaging method for regional lymph node detection, detection of residual disease after incomplete resection, and the involvement of pelvic structures in more advanced tumours.…”
Section: Introductionmentioning
confidence: 99%